Relevance of diet diversification in the coexistence between Orius laevigatus and Amblyseius swirskii: prey switching and intraguild predation - José Enrique Mendoza; Virginia Balanza; Amador Rodríguez-Gómez; Dina Cifuentes; Pablo Bielza (Journal of Pest Science, 2024)
Omnivores obtain resources from more than one trophic level, choosing food based on quantity and quality. They usually engage in intraguild predation (IGP) when prey is scarce. Orius laevigatus is an example of omnivore that becomes superior predator of the predatory mite Amblyseius swirskii when released in a combined system under low levels of the preferred prey, the thrips Frankliniella occidentalis . Here, we test two genetically enhanced O. laevigatus strains for bigger size and better fitness feeding on pollen (BIG30 and 2POL-11, respectively), hence with a wider dietary diversification, to elucidate the potential effects on prey preference and IGP on the predatory mite, in comparison with a commercial population of O. laevigatus . To do that, predation rates were registered on adult phytoseiids solely or in a choice situation at different availability ratios of adult thrips under laboratory conditions. The effect of pollen as supplemental food on IGP and prey preference was examined, too. We found that our two enhanced lines killed up to 9% less predatory mites and fed preferably on adult thrips, compared to the commercial population. While BIG30 showed a significantly higher total predation rate, killing up to 150% more adult thrips, 2POL-11 is defined as an efficient user of resources, switching between different prey and pollen showing low IGP. Pollen supplementation had a significant effect on reducing IGP, but only for 2POL-11 the influence on prey preference was significant. The theory of intraguild predation and the impact of prey switching on food webs and biological control strategies are also discussed.